Justice-Making in the Manobo and Biblical Tradition: A Contrapuntal Reading - Brazal, Agnes (The international journal of religion and spirituality in society, 2021)
Traditional comparisons of indigenous and Christian tradition usually presuppose the primacy of Christianity. This essay takes a postcolonial approach by comparing justice-making in the Manobo and Biblical tradition on equal terms using the method of contrapuntal reading. The two traditions possess elements of retributive and restorative justice. The encounter between Manobos and Christians, however, has led to the development of the law of the panavuk (damages) where instead of immediate retaliation damages are paid to restore the honor of the aggrieved and the offender. While both stress the importance of reintegrating the offender to the community, the Manobo practice of community dialogue involving the active participation of the offender, victim, and the community, is a process of restorative justice that acknowledges more the role of the community in the wrongdoing and in making things right. This in turn can challenge the retributive approach to criminal justice in the country, in particular, Filipino Christians’ toleration of extra-judicial killing that puts the blame solely on small-time drug peddlers.